Administration's Proposed NSF Budget Includes a 5.5% Increase for Geosciences. (23rd April 2013) - Showstack, Randy
Abstract : The fiscal year (FY) 2014 proposed federal budget for the U.S. National Science Foundation (NSF) is $7.63 billion, 7.3% above the FY 2012 actual amount. NSF acting director Cora Marrett said the budget reflects the administration's recognition of NSF and the importance of funding basic research. "We are pleased about where we stand and hope that Congress will be just as pleased with the budget proposal and will help move things forward, " she said during a meeting of the NSF Advisory Committee for Geosciences on 11 April. Budget comparisons are to FY 2012 because the 2013 appropriations were enacted at the end of March, less than 2 weeks before President Barack Obama sent the proposed budget to Congress.